2012
DOI: 10.1183/09059180.00009411
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar microlithiasis: two case reports and review of the literature

Abstract: Pulmonary alveolar microlithiasis is a rare diffuse lung disease characterised by deposition of calcium phosphate within the alveolar airspaces. The disease is usually discovered from birth up to 40 yrs of age and is often diagnosed incidentally during radiography of the chest for other reasons. Many patients are asymptomatic and the majority of patients either have normal or restrictive pulmonary function. The clinical course of the disease varies. While it remains static in some patients, it progresses into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 61 publications
0
40
0
4
Order By: Relevance
“…Pulmonary alveolar microlithiasis (PAM) is a rare, autosomal recessive lung disease in which calcium phosphate crystal formation in the alveolar space results in progressive radiographic opacification, pulmonary fibrosis, and respiratory failure (110). PAM is associated with consanguinity and is most common in Japan, Turkey, and Italy, with about 700 cases reported in the medical literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary alveolar microlithiasis (PAM) is a rare, autosomal recessive lung disease in which calcium phosphate crystal formation in the alveolar space results in progressive radiographic opacification, pulmonary fibrosis, and respiratory failure (110). PAM is associated with consanguinity and is most common in Japan, Turkey, and Italy, with about 700 cases reported in the medical literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Bonette et al recommended bilateral lung transplantations instead of unilateral transplants on the grounds of resistant shunt development in a lung transplantation series of 14 cases, one of which was caused by PAM 12 . Besides, no recurrence was detected in the presented cases or series 7, 8, 10, 13, 14 . Moon et al reported the case of a patient who survived for 15 postoperative years with no recurrence after the lung transplantation was performed after PAM diagnosis 8 .…”
Section: Discussionmentioning
confidence: 52%
“…Ozçelik et al have described the positive effects of the long term use of sodium etidronate which is effective by inhibiting the hydroxyapatite microcrystal formation in pediatric patients 11 . However, there are also some studies showing that the sodium etidronate treatment is ineffective 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations